2007
DOI: 10.1097/inf.0b013e31806215e3
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and C-Reactive Protein as Diagnostic Markers of Severe Bacterial Infections in Febrile Infants and Children in the Emergency Department

Abstract: Both PCT and CRP are valuable markers in predicting SBI in children with fever without source and they perform better than WBC and ANC. PCT appears more accurate at the beginning of infections, but overall CRP may be the most convenient marker for its better sensitivity and feasibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
166
8
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(212 citation statements)
references
References 40 publications
21
166
8
17
Order By: Relevance
“…First, the prevalence of SBI obtained in our study was similar to those reported in other recent European publications, 17,25,33 5 only 62% of the respondents reported using some set of published guidelines and among them, 20% cited using the Philadelphia protocol, 15% the Rochester criteria, and 13% the Boston criteria. As there seems to be no predominant criteria used in the United States and none of these classic risk criteria are frequently used in Europe, we chose the Rochester criteria for the reasons previously mentioned.…”
Section: Discussionsupporting
confidence: 76%
“…First, the prevalence of SBI obtained in our study was similar to those reported in other recent European publications, 17,25,33 5 only 62% of the respondents reported using some set of published guidelines and among them, 20% cited using the Philadelphia protocol, 15% the Rochester criteria, and 13% the Boston criteria. As there seems to be no predominant criteria used in the United States and none of these classic risk criteria are frequently used in Europe, we chose the Rochester criteria for the reasons previously mentioned.…”
Section: Discussionsupporting
confidence: 76%
“…This was in accordance with the reports of Karlsson et al 18 and Andreola et al 19 though the rate of positive culture was less than ours. Karlsson et al18 also reported of significantly higher PCT levels in positive culture cases compared to that of the negative ones.…”
supporting
confidence: 80%
“…The prognostic significance of PCT has already been established in studies with immunocompetent adult patients in ICU [9,10] and in children with febrile neutropenia [11,12]. Presumably in our patients high levels of PCT could have been due to stimulus from infecting organism which release high levels of cytokine [13] as evident from sepsis and positive blood culture reports.…”
Section: Discussionmentioning
confidence: 66%